Shiʻa Islam in colonial India: religion, community and sectarianism - Jones, Justin (Cambridge studies in Indian history and society, 2012)
Interest in Shi'a Islam has increased greatly in recent years, although Shi'ism in the Indian subcontinent has remained largely underexplored. Focusing on the influential Shi'a minority of Lucknow and the United Provinces, a region that was largely under Shi'a rule until 1856, this book traces the history of Indian Shi'ism through the colonial period toward independence in 1947. Drawing on a range of new sources, including religious writing, polemical literature and clerical biography, it assesses seminal developments including the growth of Shi'a religious activism, madrasa education, missionary activity, ritual innovation and the politicization of the Shi'a community. As a consequence of these significant religious and social transformations, a Shi'a sectarian identity developed that existed in separation from rather than in interaction with its Sunni counterparts. In this way the painful birth of modern sectarianism was initiated, the consequences of which are very much alive in South Asia today.